1976
DOI: 10.1017/s0003356100031421
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility studies with cows given whole and rolled cereal grains

Abstract: The susceptibility of whole and rolled cereal and legume seeds to microbial attack within the rumen of cows was examined by incubating seeds in nylon bags in the rumen for 24,48 and 72 hr. With whole, intact seeds the husked cereal grains were less susceptible than naked grains and legume seeds. Inter-varietal differences were observed with maize, oats and barley. Breaking the cereal grains before incubation considerably increased the losses of dry matter. Digestibility trials with non-lactating cows confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
1

Year Published

1979
1979
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 14 publications
3
15
1
1
Order By: Relevance
“…Downloaded from www.nrcresearchpress.com by 34.214.212.150 on 05/10/18 For personal use only. The observed ranking of ISDMD in sectioned grains, i.e., wheat ) barley > sorghum > maize, is in agreement with the results of Nordin and Campling (1976 (Ely et al1967) have shown that zein protein resists microbial digestion, while Peterson et al (1975) (Orskov 1986 …”
Section: Rbsultssupporting
confidence: 85%
“…Downloaded from www.nrcresearchpress.com by 34.214.212.150 on 05/10/18 For personal use only. The observed ranking of ISDMD in sectioned grains, i.e., wheat ) barley > sorghum > maize, is in agreement with the results of Nordin and Campling (1976 (Ely et al1967) have shown that zein protein resists microbial digestion, while Peterson et al (1975) (Orskov 1986 …”
Section: Rbsultssupporting
confidence: 85%
“…For cows yielding 18 to 24 kg FCM daily, Mertens (1984) calculated that the optimum NDF level in the diet was 350 g/kg; corresponding values in experiment 1 were 363, 293 and 255 g/kg for oats, barley and wheat respectively. Whole grain excretion of cows given diets A and W averaged proportionately 0-16 and this is less than half the 0-41 excretion reported by Nordin and Campling (1976). In experiment 2, the lower level of NDF in diet A (371) compared with diets W (423) or R (416 g/kg) may have contributed to the 0-10 proportionately greater FCM and 0-13 higher milk fat produced in cows given the alkali-treated oats.…”
Section: Discussionmentioning
confidence: 66%
“…It would be expected that grains which are more rapidly degraded in the rumen should be associated with a greater incidence of bloat. In this regard, Nordin and Campling (1976) reported that proportional 48-h DM losses from nylon bags incubated in the rumen were only 0-09 for whole barley, 017 to 0-31 for naked barley, and 0-85 for broken barley. 0rskov, Soliman and MacDearmid (1978) observed that proportionately less than 0-05 of whole grains were degraded in nylon bags incubated in the rumen for 36 h in comparison with 0-85 of rolled barley.…”
Section: Utilization Of Whole Grain By Cattlementioning
confidence: 99%